Hepatitis C Virus Deletion Mutants Are Found in Individuals Chronically Infected with Genotype 1 Hepatitis C Virus in Association with Age, High Viral Load and Liver Inflammatory Activity - Cheroni, Cristina (PLoS One, 2015)
Hepatitis C virus (HCV) variants characterized by genomic deletions in the structural protein region have been sporadically detected in liver and serum of hepatitis C patients. These defective genomes are capable of autonomous RNA replication and are packaged into infectious viral particles in cells co-infected with the wild-type virus. The prevalence of such forms in the chronically HCV-infected population and the impact on the severity of liver disease or treatment outcome are currently unknown. In order to determine the prevalence of HCV defective variants and to study their association with clinical characteristics, a screening campaign was performed on pre-therapy serum samples from a well-characterized cohort of previously untreated genotype 1 HCV-infected patients who received treatment with PEG-IFNα and RBV. 132 subjects were successfully analyzed for the presence of defective species exploiting a long-distance nested PCR assay. HCV forms with deletions predominantly affecting E1, E2 and p7 proteins were found in a surprising high fraction of the subjects (25/132, 19%). Their presence was associated with patient older age, higher viral load and increased necroinflammatory activity in the liver. While the presence of circulating HCV carrying deletions in the E1-p7 region did not appear to significantly influence sustained virological response rates to PEG-IFNα/RBV, our study indicates that the presence of these subgenomic HCV mutants could be associated with virological relapse in patients who did not have detectable viremia at the end of the treatment.